2007
DOI: 10.1111/j.1445-2197.2007.04127_19.x
|View full text |Cite
|
Sign up to set email alerts
|

Pr20
paediatric Nasal Fractures: Patient Satisfaction Following Closed Reduction

Abstract: PurposePost operative monitoring is crucial for the success of microsurgical free tissue transfer. Sophisticated and expensive methods are available for monitoring. We propose a novel technique using digital photography and the internet as a reliable and cost effective method to monitor free tissue transfers. Methods163 micro-vascular procedures were monitored using this technique over 8 months. Serial photographs taken to show flap color. Capillary refill time, pin prick-bleed time and color and hand held Dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Many studies have reported on the results of the reduction of a nasal bone fracture in terms of patient satisfaction or rate of complications [ 1 2 3 4 ]. However, patient satisfaction is subjective and is limited to evaluating the operation results or related factors that influenced the result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported on the results of the reduction of a nasal bone fracture in terms of patient satisfaction or rate of complications [ 1 2 3 4 ]. However, patient satisfaction is subjective and is limited to evaluating the operation results or related factors that influenced the result.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with nasal bone fractures undergo a closed reduction. However, only a few objective reports have been written on the results of a closed reduction on nasal fractures; some authors have analyzed the results using a questionnaire about a patient's satisfaction or experience with complications [ 1 2 3 4 ]. Since the nasal septum has an important role in supporting the nasal bone, a septal fracture or deviation can result in functional or esthetic problems [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…9 The goal of OCRFF for NOE defects is to provide a serviceable reconstruction that allows for adjuvant therapy administration with possibility for refinement and revision after cancer control.…”
Section: Introductionmentioning
confidence: 99%
“…Radiological investigations like X-ray nasal bone lateral view bilateral side and CT Scan nose and PNS play important role in not only accurate diagnosis of fracture nose but also post operative evaluation of accuracy of surgery. In our study patient satisfaction rate is 87.2% whereas study of Love RL [14] showed satisfaction rate 88%. Most common complication presented post operatively were hump nose, saddle nose, nasal obstruction, deviated nasal septum and anosmia [1].…”
Section: Discussionmentioning
confidence: 44%